2011
DOI: 10.1063/1.3622641
|View full text |Cite
|
Sign up to set email alerts
|

Modification of spontaneous emission rates in single colloidal CdSe/ZnS quantum dots by a submicron-sized dielectric disk

Abstract: The spontaneous emission (SE) of light sources can be modified externally by surrounding local density of optical states. Here, the SE of single colloidal CdSe/ZnS quantum dots (QDs) coupled to dielectric disks with sub-micrometer sizes was investigated. Using single-QD measurement, the radiative decay rates can be extracted based on time-tagged, time-resolved measurement. In this case, up to ∼6-fold enhancement of the SE rate was observed when single QDs were located on the disk edge. In addition, the photon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Emission behavior of QDs can flexibly be modulated by metallic surface, photonic crystals, hyperbolic metamaterials, , plasmonic nanocavities, and graphene (or carbon). It has been reported that emission intensity and emission rate of QDs were enhanced when QDs were close to the metallic surface, photonic crystals, hyperbolic metamaterials, and plasmonic nanocavities, although the mechanisms are different for different types of materials. Apart from the modulation over emission intensity and emission rate, metallic surface and nanocavities also engineer the single-photon emission behavior of QDs. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission behavior of QDs can flexibly be modulated by metallic surface, photonic crystals, hyperbolic metamaterials, , plasmonic nanocavities, and graphene (or carbon). It has been reported that emission intensity and emission rate of QDs were enhanced when QDs were close to the metallic surface, photonic crystals, hyperbolic metamaterials, and plasmonic nanocavities, although the mechanisms are different for different types of materials. Apart from the modulation over emission intensity and emission rate, metallic surface and nanocavities also engineer the single-photon emission behavior of QDs. , …”
Section: Introductionmentioning
confidence: 99%
“…Colloidal quantum dots (QDs), a zero-dimensional quantum emitter, have drawn intense attention over the past two decades because of their interesting optical properties, superior quantum yield, high emission intensity, and single-photon emission at room temperature. QDs have been used to investigate the modulation and engineering of spontaneous emission, which is regarded as the heart of nano-optics and photonics, and has significant implications in the fields of energy, communication, and quantum optics. Emission behavior of QDs can flexibly be modulated by metallic surface, photonic crystals, hyperbolic metamaterials, , plasmonic nanocavities, and graphene (or carbon). It has been reported that emission intensity and emission rate of QDs were enhanced when QDs were close to the metallic surface, photonic crystals, hyperbolic metamaterials, and plasmonic nanocavities, although the mechanisms are different for different types of materials. Apart from the modulation over emission intensity and emission rate, metallic surface and nanocavities also engineer the single-photon emission behavior of QDs. , …”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of spontaneous emission rates can be described by the Purcell factor, which is proportional to the ratios between the cavity quality factor, Q , and mode volume, V ( F P ∝ Q / V ) . For conventional dielectric cavities, for example, a microdisk cavity or photonic crystal, they can provide a large quality factor, but the mode volume is restricted by the diffraction limit . In addition, their resonance band is extremely narrow and thus can only couple to a single emission frequency (for example, X or BX emission) with narrow spectral line width.…”
Section: Introductionmentioning
confidence: 99%
“…Q is the quality factor of the combined quantum dot-cavity system, given by Q = λ peak /( λ cav + λ QD ), where λ cav and λ QD are the homogeneous line widths of the cavity mode and the quantum dot emission, respectively [30,31]. In these room temperature experiments, λ cav ≈ 0.1 nm and λ QD ≈ 14 nm, so the relevant Q factor is approximately 45, determined by the exciton dephasing rate of the quantum dots.…”
mentioning
confidence: 99%